Structural Diversities of Lectins Binding to the Glycosphingolipid Gb3 - Siukstaite, Lina; Imberty, Anne; Römer, Winfried (Frontiers in Molecular Biosciences, 2021)
Glycolipids are present on the surfaces of all living cells and thereby represent targets for many protein receptors, such as lectins. Understanding the interactions between lectins and glycolipids is essential for investigating the functions of lectins and the dynamics of glycolipids in living membranes. This review focuses on lectins binding to the glycosphingolipid globotriaosylceramide (Gb3), an attractive host cell receptor, particularly for pathogens and pathogenic products. Shiga toxin (Stx), from Shigella dysenteriae or Escherichia coli, which is one of the most virulent bacterial toxins, binds and clusters Gb3, leading to local negative membrane curvature and the formation of tubular plasma membrane invaginations as the initial step for clathrin-independent endocytosis. After internalization, it is embracing the retrograde transport pathway. In comparison, the homotetrameric lectin LecA from Pseudomonas aeruginosa can also bind to Gb3, triggering the so-called lipid zipper mechanism, which results in membrane engulfment of the bacterium as an important step for its cellular uptake. Notably, both lectins bind to Gb3 but induce distinct plasma membrane domains and exploit mainly different transport pathways. Not only, several other Gb3-binding lectins have been described from bacterial origins, such as the adhesins SadP (from Streptococcus suis) and PapG (from E. coli), but also from animal, fungal, or plant origins. The variety of amino acid sequences and folds demonstrates the structural versatilities of Gb3-binding lectins and asks the question of the evolution of specificity and carbohydrate recognition in different kingdoms of life.